2014
DOI: 10.1515/cipms-2015-0013
|View full text |Cite
|
Sign up to set email alerts
|

Compressional, mechanical and release properties of a novel gum in paracetamol tablet formulations

Abstract: The binding properties of Eucalyptus gum obtained from the incised trunk of Eucalyptus tereticornis, were evaluated in paracetamol tablet formulations, in comparison with that of Gelatin B.P. In so doing, the compression properties were analyzed using density measurements and the compression equations of Heckel, Kawakita and Gurham. In our work, the mechanical properties of the tablets were assessed using the crushing strength and friability of the tablets, while the drug release properties of the tablets were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…The gum was purified using previously described methods. 11,12 Briefly, the exudate was hydrated in a 0.5 : 95.5 (v/v) CHCl 3 /water mixture for five days with intermittent stirring; extraneous materials were removed by straining through a muslin cloth. Absolute ethanol was used to precipitate the gum from the solution.…”
Section: Preparation Of the Gummentioning
confidence: 99%
See 1 more Smart Citation
“…The gum was purified using previously described methods. 11,12 Briefly, the exudate was hydrated in a 0.5 : 95.5 (v/v) CHCl 3 /water mixture for five days with intermittent stirring; extraneous materials were removed by straining through a muslin cloth. Absolute ethanol was used to precipitate the gum from the solution.…”
Section: Preparation Of the Gummentioning
confidence: 99%
“…CSFR has been described as a useful index for tablet quality. 12 Also, Bamiro et al reported that the higher the value of this index, the stronger the tablet. 24 The results obtained (Table 4) generally showed an increase in CSFR and hence, tablet strength, as binder and HPMC concentrations increased.…”
Section: Evaluation Of Naproxen Tablet Formulationsmentioning
confidence: 99%
“…This means that the equation may be used to interpret the densification mechanisms of the ibuprofen tablet formulation . The Kawakita parameter P k , is an inverse measure of the total amount of plastic deformation in the compression process . A lower P k value is an indication of better or increased total plastic deformation …”
Section: Resultsmentioning
confidence: 99%
“…The plant was authenticated in the herbarium facility of the Faculty of Pharmacy, University of Uyo, Nigeria and the voucher number of authentication is UUPH8 (eii). The gum was purified using an established procedure [10,15,16]. The raw Raffia gum was hydrated in 0.5: 95.5 (v/v) chloroform water mixture for 5 d with intermittent stirring; extraneous materials were removed by straining through a piece of calico cloth.…”
Section: Gum Extractionmentioning
confidence: 99%